2014
DOI: 10.1038/pr.2014.156
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum subspecies infantis: champion colonizer of the infant gut

Abstract: Oligosaccharides are abundant in human milk. Production of these highly diverse structures requires significant energy expenditure by the mother and yet these human milk oligosaccharides offer no direct nutritive value to her infant. A primary function of human milk oligosaccharides is to shape the infant’s intestinal microbiota with life-long consequences. Bifidobacterium longum subspecies infantis (B. infantis) is unique among gut bacteria in its prodigious capacity to digest and consume any human milk oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
292
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(315 citation statements)
references
References 82 publications
(84 reference statements)
11
292
1
11
Order By: Relevance
“…We showed that Bifidobacterium infantis effectively degraded the full range of the low molecular weight HMOS structures including neutral trioses, tetraoses, and pentaoses as well as acidic trioses. This is consistent with the unique HMOS utilisation capability of Bifidobacterium infantis by encoding a 43kb gene cluster that carries the genes for different oligosaccharides transport proteins and glycosyl hydrolases (Underwood et al 2014). No signal peptide or transmembrane domain was predicted for Bifidobacterium infantis enzymes involved in the cleavage of the monitored HMOS structures (Table S2), indicating intracellular degradation of these substrates.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We showed that Bifidobacterium infantis effectively degraded the full range of the low molecular weight HMOS structures including neutral trioses, tetraoses, and pentaoses as well as acidic trioses. This is consistent with the unique HMOS utilisation capability of Bifidobacterium infantis by encoding a 43kb gene cluster that carries the genes for different oligosaccharides transport proteins and glycosyl hydrolases (Underwood et al 2014). No signal peptide or transmembrane domain was predicted for Bifidobacterium infantis enzymes involved in the cleavage of the monitored HMOS structures (Table S2), indicating intracellular degradation of these substrates.…”
Section: Discussionsupporting
confidence: 75%
“…Despite the structural similarity between mucins and HMOS ( Fig. 1), only some Bifidobacterium species, particularly Bifidobacterium bifidum strains can utilise mucins for growth (Marcobal et al 2013, Underwood et al 2014.…”
Section: Chaptermentioning
confidence: 99%
“…Although 2ʹFL is utilized by B. infantis as well as some strains of B. longum subsp. longum and B. breve 46,47 , the ecological context (that is, infants versus adults) might dictate whether these HMOs are indeed pre biotic. Moreover, having structural equivalence to specific HMOs does not infer functional equiva lence to the con stellation of HMOs in milk 48 .…”
Section: Box 2 | Justification For the New Definition Of Prebioticsmentioning
confidence: 99%
“…A single subspecies, Bifidobacterium longum subsp. infantis has evolved the capacity to transport and consume all the various HMO structures, providing it with a significant advantage in colonization over other gut microbes [45]. It is likely that the prebiotic HMOs, which are produced at significant cost to the mother, play a significant role in many of the observed beneficial effects of human milk.…”
Section: Prebiotics For Term Infantsmentioning
confidence: 99%